Optimization of a low-cost defined medium for alcoholic fermentation – a case study for potential application in bioethanol production from industrial wastewaters - Comelli, Raul Nicolas (2015)
In bioethanol production processes, the media composition has an impact on product concentration, yields and the overall process economics. The main purpose of this research was to develop a low-cost mineral-based supplement for successful alcoholic fermentation in an attempt to provide an economically feasible alternative to produce bioethanol from novel sources, e.g., sugary industrial wastewaters. Statistical experimental designs were used to select essential nutrients for yeast fermentation, and its optimal concentrations were estimated by Response Surface Methodology. Fermentations were performed on synthetic media inoculated with 2.0 g/L of yeast, and the evolution of biomass, sugar, ethanol, CO2 and glycerol were monitored over time. A mix of salts [10.6 g/L (NH4)2HPO4; 6.4 g/L MgSO4.7H2O and 7.5 mg/L ZnSO4.7H2O] was found to be optimal. It led to the complete fermentation of the sugars in less than 12 h with an average ethanol yield of 0.42 gethanol/gsugar. A general C-balance indicated that no carbonaceous compounds different from biomass, ethanol, CO2 or glycerol were produced in significant amounts in the fermentation process. Similar results were obtained when soft drink wastewaters were tested to evaluate the potential industrial application of this supplement. The ethanol yields were very close to those obtained when yeast extract was used as the supplement, but the optimized mineral-based medium is six times cheaper, which favorably impacts the process economics and makes this supplement more attractive from an industrial viewpoint.